Fabrication of high-efficiency PET polymer-based flexible dye-sensitized solar cells and tapes via heat sink-supported thermal sintering of bilayer TiO2 photoanodes. Issue 10 (21st April 2022) - Murali, B.; Gireesh Baiju, K.; Krishna Prasad, R.; Jayanarayanan, K.; Kumaresan, Duraisamy
Abstract : This work introduces a new type of high temperature material processing technique for the preparation of a bilayer TiO2 -coated ITO PET polymer photoanode of flexible dye-sensitized solar cells producing a maximum power conversion efficiency of 6.33%. Abstract : This work introduces a new type of elevated temperature material processing technique for the preparation of a bilayer TiO2 -coated ITO PET (indium tin oxide polyethylene terephthalate) polymer photoanode of flexible dye-sensitized solar cells (FDSSCs) producing a maximum power conversion efficiency (PCE) of 6.33%. In this process, TiO2 nanoscale and mesoscale layers are deposited sequentially onto a flexible ITO PET polymer and sintered in the presence of a chiller + heat sink + compression press heating system (hot plate). The chiller reduces the heat sink surface temperature up to −14 °C, while the interconnection of TiO2 layers kept between the heat sink and hot plate develops by mild sintering at 250 °C. As a result, the bilayer FDSSC photoanode prepared via this process has showed the highest photocurrent density of 15.91 ± 0.17 mA cm −2 and an open circuit voltage of 0.71 V, surpassing the other literature reported values of PET polymer-based FDSSCs. Besides, as part of the device engineering, different TiO2 nanostructures such as TiO2 nanoparticles (TNP) and TiO2 nanowires (TNW) have been employed as mesoscale light scattering layers in the bilayer photoanodes of FDSSCs. The photovoltaic current density–voltage ( J – V ) and electrochemical impedance studies have confirmed the superiority of one-dimensional TNW structures with greater charge transport and light scattering ability for significantly improving the photovoltaic performances of the laboratory-scale FDSSCs and large-area FDSSC tapes/rolls.